2011
DOI: 10.4093/dmj.2011.35.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Clinical Parameters for the Therapeutic Efficacy of Sitagliptin in Korean Type 2 Diabetes Mellitus

Abstract: BackgroundSitagliptin is a highly selective dipeptidyl peptide-4 (DPP-4) inhibitor that increases blood levels of active glucagon-like peptide (GLP)-1 and glucose-dependent insulinotrophic polypeptide (GIP), resulting in increased insulin secretion. While studies conducted in other countries have indicated the efficacy and safety of using sitagliptin to treat type 2 diabetes mellitus (T2DM), its predictors of effects to sitagliptin are not well understood. Therefore, we evaluated the predictive clinical parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 20 publications
5
40
1
Order By: Relevance
“…However, Kim et al reported that sitagliptin responders had lower BMI and were younger than non-responders in Korean patients with type 2 diabetes [12]. Nomiyama et al reported that treatment with sitagliptin 50 mg/day for 24 weeks in a larger number of patients was especially effective in patients with higher baseline HbA1c, lower BMI, and shorter duration of diabetes [13] and similar results were reported by Maeda et al [14].…”
Section: Discussionsupporting
confidence: 69%
“…However, Kim et al reported that sitagliptin responders had lower BMI and were younger than non-responders in Korean patients with type 2 diabetes [12]. Nomiyama et al reported that treatment with sitagliptin 50 mg/day for 24 weeks in a larger number of patients was especially effective in patients with higher baseline HbA1c, lower BMI, and shorter duration of diabetes [13] and similar results were reported by Maeda et al [14].…”
Section: Discussionsupporting
confidence: 69%
“…Among those, however, 18% patients revealed no reduction or even the increase of HbA1c levels after 3 months' sitagliptin treatment, comparable to the report from Korea [12]. After the stratification of patients into three groups according to the degree of HbA1c reduction, candidate factors were listed and evaluated in relation to the glucose-lowering effect of sitagliptin.…”
Section: Conflict Of Interestmentioning
confidence: 57%
“…Moreover, as reported by Jones et al [18], the addition of rosiglitazone to metformin was most effective in obese, insulin-resistant patients with type 2 diabetes. In DPP-4 inhibitors treated patients, two studies in Japanese patients [19] and in Korean T2DM subjects [20] suggested that DPP-4 inhibitor treatment efficacy was associated with a low baseline BMI. In GLP-1 receptor agonists treated patients, a study designed to identify predictors of response to liraglutide therapy in Japanese patients [21] concluded that the efficacy of liraglutide could be associated with BMI at baseline.…”
Section: Discussionmentioning
confidence: 99%